REFORMATION OF LAW ENFORCEMENT OF CYBER CRIME IN INDONESIA - Bambang Tri Bawono (Jurnal Pembaharuan Hukum, 2019)
Technological progress and the presence of globalization in third world countries including Indonesia has a variety of consequences, this includes the negative impact of increasing cybercrime in Indonesia. Increasing cybercrime in the community with a variety of increasingly sophisticated modus operandi, in reality, is not balanced by the existence of a comprehensive legal umbrella, and also the absence of adequate facilities and pre-facilities is a separate issue in the enforcement of cybercrime cases in a dynamic society. Enforcement weaknesses are the lack of human resources of investigators who understand cybercrime and the lack of means and pre-law enforcement facilities in cybercrime. so it is necessary to increase the HR of the relevant law enforcers as well as the improvement of facilities and pre-facilities related to law enforcement in cybercrime. Enforcement weaknesses are the lack of human resources of investigators who understand cybercrime and the lack of means and pre-law enforcement facilities in cybercrime. So it is necessary to increase the HR of the relevant law enforcers as well as the improvement of facilities and facilities related to law enforcement in cybercrime.